Soybean DICER-LIKE2 Regulates Seed Coat Color via Production of Primary 22-Nucleotide Small Interfering RNAs from Long Inverted Repeats. Issue 12 (19th October 2020) - Jia, Jinbu; Ji, Ronghuan; Li, Zhuowen; Yu, Yiming; Nakano, Mayumi; Long, Yanping; Feng, Li; Qin, Chao; Lu, Dongdong; Zhan, Junpeng; Xia, Rui; Meyers, Blake C.; et al.
Abstract : Soybean DCL2 favors long inverted repeat-derived double-stranded RNA as its substrate and generates primary 22-nucleotide siRNAs to regulate seed coat color and silence transposable elements. Abstract: In plants, 22-nucleotide small RNAs trigger the production of secondary small interfering RNAs (siRNAs) and enhance silencing. DICER-LIKE2 (DCL2)-dependent 22-nucleotide siRNAs are rare in Arabidopsis ( Arabidopsis thaliana ) and are thought to function mainly during viral infection; by contrast, these siRNAs are abundant in many crops such as soybean ( Glycine max ) and maize ( Zea mays ). Here, we studied soybean 22-nucleotide siRNAs by applying CRISPR-Cas9 to simultaneously knock out the two copies of soybean DCL2, GmDCL2a and GmDCL2b, in the Tianlong1 cultivar. Small RNA sequencing revealed that most 22-nucleotide siRNAs are derived from long inverted repeats (LIRs) and disappeared in the Gmdcl2a/2b double mutant. De novo assembly of a Tianlong1 reference genome and transcriptome profiling identified an intronic LIR formed by the chalcone synthase (CHS) genes CHS1 and CHS3 . This LIR is the source of primary 22-nucleotide siRNAs that target other CHS genes and trigger the production of secondary 21-nucleotide siRNAs. Disruption of this process in Gmdcl2a/2b mutants substantially increased CHS mRNA levels in the seed coat, thus changing the coat color from yellow to brown. Our results demonstrated that endogenous LIR-derived transcripts in soybean are predominantly processed by GmDCL2 into 22-nucleotide siRNAs and uncovered a role for DCL2 in regulating natural traits.